Intracerebroventricular microinjection of the 5-HT 1F receptor agonist LY 344864 inhibits methamphetamine conditioned place preference reinstatement in rats - Shahidi, Siamak; Sadeghian, Reihaneh; Komaki, Alireza; Asl, Sara Soleimani (Pharmacology, biochemistry and behavior, 2018)
Relapse following a prolonged period of drug cessation is a key barrier in the treatment of methamphetamine (METH) addiction, for which pharmacological treatment exhibits little efficacy. Previous studies have suggested that this process involves alterations in levels of serotonin (5-HT) in the brain. Although the 5-HT receptor has been implicated in the reward pathway, its physiological functions remain unknown. In the present study, we examined the effect of the 5-HT agonist LY 344864 on the reinstatement of METH-seeking behavior in rats using a conditioned place preference (CPP) paradigm. The CPP paradigm was first used to determine the effective doses of LY and METH. Four groups were then conditioned with METH (5 mg/kg; i.p.), while the sham group received saline. METH-induced CPP was subsequently extinguished. On the 13th day of extinction, the rats received either METH (0, 1, or 2.5 mg/kg; i.p.) plus vehicle or priming METH plus LY (2 μg/5 μL; i.c.v.). On reinstatement day, preference scores were calculated as the difference in time spent in the drug-paired and vehicle-paired compartments. Rats conditioned with the lowest effective dose of METH (5 mg/kg) exhibited significant differences in pre- and post-testing preference scores. Preference scores were significantly higher in the saline + METH group than in the control group. Furthermore, preference scores were significantly higher in rats that had received priming METH treatment, and pre-treatment with LY significantly attenuated the reinstatement of METH-seeking behavior. These findings suggest that future studies should evaluate the therapeutic potential of 5-HT agonists for preventing relapse in individuals with METH addiction.